Associations Between a Targeted Metabolomics Panel of Urinary Flavonoids and Flavonoid Intakes from Fruits and Vegetables Across Dietary Assessment Periods. (7th June 2021) - Hill, Emily; Pashkova, Anna; Grainger, Elizabeth; Roberts, Kristen; Chitchumroonchokchai, Chureeporn; Clinton, Steven; Spees, Colleen
Abstract: Objectives: Aligning dietary intake and food composition data with biomarkers of exposure is critical for advancing assessment methodology. Flavonoids present in fruits and vegetables (FV) are rapidly metabolized and excreted in urine; therefore they may serve as acute intake biomarkers. Yet, the optimal dietary assessment period has not been determined. The objective of this study was to evaluate associations between a targeted metabolomics panel of six urinary flavonoids and dietary intakes of these flavonoids from FV across varying dietary assessment periods. Methods: In this cross-sectional study, three-day diet records from 17 individuals were analyzed via Nutrition Data System for Research to determine FV intakes over one-day, two-day, and three-day assessment periods. Dietary flavonoids from FV were estimated via the Phenol-Explorer database; total intakes of targeted flavonoids (quercetin, kaempferol, isorhamnetin, phloretin, naringenin, hesperetin) were calculated by summing aglycone and glycosylated forms. Twenty-four-hour (24-h) urine was collected on the final day of diet records. Urinary flavonoid aglycones were quantified using HPLC; total urinary flavonoids were calculated by summing targeted flavonoids. Spearman correlations between flavonoid intakes and urinary flavonoids were analyzed by dietary assessment period. Results: Mean targeted flavonoid intake from FV was 53.6 mg/day. Ten specific FV provided >95% of dietary flavonoids, with greatest contributions from citrus (orange juice, grapefruit, orange) and onion. Mean urinary flavonoid excretion was 9.5 μmol/24-h. Urinary flavonoids were moderately associated with flavonoid intakes from the one-day assessment period on the day prior to urine collection (rs  = 0.485, P  = 0.048) and summed intakes from the two-day assessment period (rs  = 0.598, P  = 0.011), but not from intakes over the three-day assessment period. Conclusions: Urinary flavonoids are most strongly associated with dietary flavonoids consumed within two days of 24-h urine collection, indicating two-day diet records aligned with 24-h urine collection is optimal for assessing (poly)phenol exposure from FV in future research. Funding Sources: OSU CCTS, Rosita Schiller Award, OSU Comprehensive Cancer Center MCC Program, and OSU CAFFRE.